Cl− Doping Strategy to Boost the Lithium Storage Performance of Lithium Titanium Phosphate - Luo, Hao; Tang, Yijun; Xiang, Zeying; Wu, Pinghui; Li, Zhizhong (Frontiers in Chemistry, 2020)
Because of energy storage limitations and the high demand for energy, aqueous rechargeable lithium batteries (ARLBs) are receiving widespread attention due to their excellent performance and high safety. Lithium titanium phosphate (LiTi2(PO4)3) exhibits the potential to serve as anodes for ARLBs because it has a three-dimensional channel and a stable structure. We employed an anion (Cl-) doping strategy to boost the lithium storage performance of LiTi2(PO4)3. A series of LiTi2(PO4)3/C composites doped by Cl- on PO43- were successfully synthesized with a sol-gel technique as anodes for ARLBs. The effects of chlorine doping with different content on the properties of LiTi2(PO4)3-xCl3x/C (x = 0.05, 0.10, and 0.15) were investigated systematically. The doping of chlorine with appropriate amounts did not significantly impact the main structure and morphology of LiTi2(PO4)3/C. However, chlorine doping greatly increased the performance of LiTi2(PO4)3/C. LiTi2(PO4)2.9Cl0.3/C (LCl-10) showed the best electrochemical properties. It delivered a discharge capacity of 108.5 and 85.5 mAh g-1 at 0.5 C and 15 C, respectively, with the increase of 13.2 and 43.3 mAh g-1 compared to blank LiTi2(PO4)3 (LCl). In addition, the discharge capacity of LCl-10 was maintained at 61.3% after 1,000 cycles at 5 C, implying an apparent improvement compared to LCl (35.3%). Our study showed that a chlorine-doped LiTi2(PO4)3/C composite is a potential anode for high-performance ARLBs.